The Horror Chamber: Unqualified Impunity in Prison - Hogle, Charles (2018)
The federal courts have been open to prisoners’ constitutional claims for half a century, but to this day, the availability of federal litigation has not stopped prisoners from being tortured, maimed, killed, or otherwise made to suffer chilling abuse. The failure of litigation as a deterrent is due in part to a confluence of legal and situational factors—doctrinal deference, statutory hurdles, and the many difficulties associated with litigating a civil rights case against one’s jailers—that make prison-conditions cases virtually impossible to win. We call this combination of factors “practical immunity.” Practical immunity amounts to a formidable barrier against successful prison-conditions cases. When practical immunity is combined with the well-known doctrine of qualified immunity, it makes the threat of a money judgment against prison defendants almost empty. The Supreme Court’s failure to take stock of practical immunity may help to explain why the landscape is so skewed against prisoners, and why prison officials enjoy a legal regime so forgiving that it borders on de facto absolute immunity